Relações entre índices urbanísticos da forma urbana e a acústica ambiental - Mendonça, André Bressa Donato (Universidade Federal de São Carlos, 2013)
Noise pollution in urban areas has been an usual problem in several Brazilian cities. However, this issue does not take into account the urban morphology and its constant changes. Therefore, sound mapping is a helping tool on the matter, allowing the prevention of sound impacts and the recognition of areas under acoustic conflicts. Applying this planning instrument, this research aims at the identification of relations between indexes of urban form and sound pressure levels achieved on street networks, specifically when considering the potential offered by the occupancy rate, the floor space index and the ratio between height and width of the urban roads. The methodology is based on the collection of physical and acoustical data, on the application of a calculation model, named NMPB-Routes 2008 and its respective validation, and on the simulation of a future scenario in the acoustic software CADNA-A. The analyzes were based on the variations of sound pressure levels, which were verified between the current scenario and the future scenario, together with the identification of the relationships between the occupancy rate, the floor space index and the H/W factor, besides the classification of the acoustics conditions of the urban blocks. The results showed that the new buildings of the future scenario contributed up to 1.0 dB (A) in the increase of the sound pressure levels at the height of ten meters above ground level. Furthermore, among the factors studied at the height of four meters, the occupancy rate is the one assuming the highest importance on the increase of sound pressure levels. On the other hand, at ten meters-high, the floor space index achieved the greatest significance in the role played on the increment of noise levels.
Keywords: Planejamento urbano; Índices urbanísticos; Acústica arquitetônica; Mapeamento sonoro; Acústica ambiental; Urban index; Environmental acoustics; Urban planning; Sound mapping; ENGENHARIAS::ENGENHARIA CIVIL